Genome-wide association studies in elite Japanese athletes - Kozuma, A.; Zempo, H.; Saito, M.; Homma, H.; de Almeida, K. Y.; Deguchi, M.; Matsumoto, S.; Matsumoto, R.; Okamoto, T.; Nakazato, K.; Kikuchi, N. (29th Annual Congress of the European College of Sport Science, 2-5 July 2024, Book of Abstracts, 2024)
INTRODUCTION: The heritability of athlete status is estimated at 66% (De Moor et al., 2007). In addition, 253 gene polymorphisms have been reported to be associated with athlete status (Semenova et al., 2023). In this study, we aimed to perform genome-wide association studies (GWAS) in elite Japanese wrestlers to identify novel gene polymorphisms (Study 1) and to replicate the novel gene polymorphisms in another cohort of Japanese wrestlers and elite Japanese weightlifters (Study 2). METHODS: Study 1 enrolled 41 highly elite wrestlers (35 men and 6 women) who participated in the Olympic games and senior international competitions, and 306 controls (143 men and 163 women). Total DNA was extracted from saliva samples using an Oragene-DNA kit. The subject`s gene polymorphisms were genotyped*by the Japonica Array v2. This study was a case-control study, with p < 5×10** considered statistically significant and the p < 5×10** was considered as a suggestive line. Study 2 of the replication cohort included 40 elite wrestlers (31 men and 9 women) from the national competition level and 69 elite weightlifters (38 men and 31 women) from the international competition level (including Olympic games). Targeted controls and genotyping used the same methods as in Study 1. Statistical significance was set at p < 0.05. RESULTS: The GWAS results of Study 1 identified 31 gene polymorphisms that reached p < 5×10** and 487 SNPs that reached p < 5×10**. The identified gene polymorphisms were then divided into 69 regions. The top gene polymorphism was the RBPMS gene rs3116007 polymorphism (p = 8.67×10**, T allele), located on chromosome 8 and encoding a member of the RNA recognition motif family. Replicated in Study 2, the RBPMS gene rs3116007 polymorphism showed a trend indicating a potential association in elite wrestlers (p = 0.081, T allele) and a significant difference in elite weightlifters compared to controls (p = 0.022, T allele). CONCLUSION: Our results identified novel gene polymorphisms associated with high elite Japanese wrestlers. In addition, RBPMS gene rs3116007 polymorphism was similarly trended in elite wrestlers and elite weightlifters.